Applying Mathematical Monetary Policy Rules in Algeria: Tylor’s Rule - Khaldoun1, Yousouf Chemseddin; Bouali, Abdelkader; Meliani, Yassine (Finance and Business Economies Review, 2023)
In this paper, we studied how far the monetary policy in Algeria is submitted to mathematical rules, and if the Bank of Algeria really adopt the augmented Taylor rule in the inflation targeting process and its effectiveness. We concluded that the latter is ineffective and that the Taylor rule does not explain the behaviour of monetary policy in Algeria due to the absence of the success factors, such as a high degree of transparency and accountability about monetary policy, in addition to the credibility of the central bank and its independence from all pressures that would deviate monetary policy from the desired objectives